Spatial analysis of hypothyroidism and ground water pH in an Urban Area of Kerala using the geographic information system - Mathew Joseph Valamparampil; Sara Varghese; Ananth Mohan; Rajesh Reghunath; A L Achu; T S Anish (Wolters Kluwer Medknow Publications, 2020)
Hypothyroidism is a disease assuming increasing relevance. The causative role of acidic nature of drinking water has not yet been investigated in Kerala. We attempted to determine the spatial association between the occurrence of self-reported hypothyroidism and pH of ground water using the geographic information system. The cross-sectional study was conducted among 1649 individuals residing in the subcenter area in urban Trivandrum. Self-reported hypothyroidism was obtained by the interview. Differential Global Positioning System was used to record the location of each house and its drinking water source. PH of 50 open-well water samples was estimated. The prevalence of self-reported hypothyroidism was 4.24%. Maps depicting pH distribution and occurrence of hypothyroidism were prepared. Most of the areas had acidic ground water. Geo-statistical analysis revealed the occurrence of statistically significant clustering of hypothyroid individuals in areas having acidic ground water. The study brings out possible linkage between hypothyroidism and acidic water intake necessitating detailed epidemiological investigations for drawing more robust associations.